Analysis of the Aircraft’s Technology as Cost Determinant in the Brazilian Sector of Commercial Aviation - Diehl, Carlos Alberto; Miotto, Genossi Rauch; Souza, Marcos Antônio (Review of Business Management, 2010)
<!–[if gte mso 9]> Normal 0 21 false false false PT-BR X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–> <!–[if gte mso 10]> <![endif]–> The objective of this study is to analyze the aircraft’s technology as determinant of costs, investigating its effect in Brazilian commercial aviation companies in the period of 1997 to 2005. It comprises the demonstration of the results of a research that presents the strategic management of costs and its contributions for the attainment of competitive advantage of Brazilian companies in the sector of commercial aviation. Of exploratory nature and longitudinal characteristic, it makes use of the documental research for data collection. For presentation and analysis of data descriptive statistic was used. The findings indicate that aircraft’s technology as determinant of costs has direct influence in the main costs of the sector: the fuel consumption, the cost of maintenance and depreciation or lease of aircraft. GOL Company has demonstrated success when lining up the aircraft’s technology and presented the less costs among the searched companies. TAM Company reorganized its aircraft fleet and reduced significantly its costs. In the case of VASP Company, which works with scrap aircraft, incurred into significantly higher costs than the others companies analyzed. Key words: Strategic cost management. Costs determinants. Commercial aviation.